VD_FINDINFO AI 232/10 - 41/2011 vom 13. Dezember 2010 - VD Tribunal cantonal (2010)
REFUS DE LA PRESTATION D'ASSURANCE, INDEMNITÉ JOURNALIÈRE, ASSURANCE-VIEILLESSE, SURVIVANTS ET INVALIDITÉ | 14a LAI, 22 LAI, 8 LAI, 78 LPGA, 18 RAI